NLP as Individual Programming:: A Comparative Analysis of Shakespeare’s Hamlet and Bachtyar Ali’s The City of White Musicians (Raparin Journal of Humanities (RJH), 2024)
The current study is an attempt to analyze two literary texts, namely William Shakespeare's play Hamlet and Bachtyar Ali's Kurdish novel The City of White Musicians, in the light of, neurolinguistics as an individual programming. These are from two distinct literary traditions that were picked because they essentially share the appearance of ghosts. To find out how these subtleties affect the reader's understanding, neurolinguistics is applied. Consequently, the paper's title was chosen. The texts serve as a sort of manual, and our goal is to identify the link that connects language and reason. These pieces are meant to affect the reader both while they are written and after. As a result, the influence is similar to programming and adheres to one of the core ideas of neurolinguistics, which will be covered in the introduction. The research tries to answer issues like The extent to which literary works' particular programming and neurolinguistics influence readers. Likewise, how "reaching success," one of the fundamental ideas of programming, is perceived. Moreover, Are there any similarities between the English and Kurdish texts in terms of neurolinguistics and personal programming? The methodology of the research is a thematic analysis method that is through studying the language and special terms from a variety of perspectives to illustrate the personal programming that is present in the texts and forms the main body of this study. One of programming's core principles is that success serves as a focus point for the procedures, according to the study's major findings. Additionally, self-criticism and the will to succeed are two other neurolinguistics foundations that are present in both texts.